Reversible switching performance of water droplet-driven triboelectric nanogenerators using a magnetocontrollable lubricant-infused surface for sustainable power generation. (1st December 2022) - Yun, Soyeon; Cho, Suhyeon; Kim, Hyeon Woo; Cho, Sung Beom; Lee, Seunghyup; Yong, Kijung
Abstract: Triboelectric nanogenerators (TENGs) are attracting great attention as potential renewable power sources; in particular, water droplet-driven liquid–solid (LS) TENGs are highly useful due to their abundant sources in daily life. This study developed a novel approach for switching the LS triboelectrification by using a magnetocontrollable lubricant-infused surface (MCLIS). The basic units of the MCLIS-based TENG (MCLIS-TENG), that is, magnetocontrollable microwires, showed different alignment states, i.e., vertically standing or lying down, depending on the direction of the applied magnetic field. These reversible wetting states generated distinctive voltage outputs of ∼2 V (ON state) and < 0.5 V (OFF state), correspondingly. ON/OFF cycles revealed excellent reversibility and stability even after 90 cycles. The switching characteristics of the MCLIS-TENG were studied systematically by varying the Weber number, inclination angle, and lubricant thickness. The proposed device also demonstrated highly sustainable power generation by utilizing the switchable wetting states even under high humidity, where the performance of most LS-TENGs degraded due to surface wetting problems. In addition, the MCLIS-TENG based self-powered magnetic proximity sensor is proposed as an exemplary application to detect the magnetic field intensity and the location of sensing object. This work provides a new idea of magnetoresponsive triboelectric switching, widening the TENG usability in low-power-consumption applications such as wireless switches and self-powered sensors. Graphical Abstract: This study presents a novel approach for switching liquid-solid triboelectrification by using a magnetocontrollable lubricant-infused surface (MCLIS). The magnetocontrollable microwires switch their alignment reversibly as the direction of magnetic field changes. This structural switching characteristic causes triboelectric switching, which makes the difference in electrical output about three times. The triboelectric switching cycles of MCLIS-TENG show good reversibility and stability. Our work provides a new idea of magnetoresponsive triboelectric switching, widening the TENG's usability in low-power-consumption applications. ga1 Highlights: A magnetocontrollable lubricant-infused surface (MCLIS) based triboelectricity. Reversible triboelectric switching by converting the MCLIS states (ON/OFF). Systemic analysis of the switching characteristics for future applications. Application of the MCLIS-TENG as a self-powered magnetic proximity sensor.